#TITLE_ALTERNATIVE# - Huda (NIM 23198032), Syamsul
ABSTRACT: The existence of an elastic member in a mechanism results in a system governed by second order nonlinear differential equations with time varying coefficients. Such systems, may become unstable at several frequency bands due to parametric excitation. This research investigated the dynamics behavior of elastic slider-crank, four-bar and quick-return mechanisms. The stability are evaluated for several values of crank-to-coupler ratio, ratio of mass of elastic member to that of the follower, S, at various angular velocity, w. In addition, the effects of damping and external force on the stability were also studied. Prior to stability analysis and dynamic response evaluation, the governing equations of motion were .first linearized by Perturbation method. The stability analysis is based upon Floquet Theory while the dynamic resjxmse was obtained via a numerical steady-state solution algorithm developed by discretizing the parameters continua. The results show the parametric instability may occur even at relatively low speed, especially for high amplitude of excitation represented by the crank-to-coupler ratio, u. Higher elastic member mass results in less stable mechanism, while damping reduces the instabilitty.